Transnacionalidad e intertextualidad en El cóndor de Père-Lachaise de Fernando Iwasaki - Juan Luis Roldán Romero (Recherches)
Fernando Iwasaki Cauti (1961), a Peruvian writer based in Seville since the 1990s, is one of the many authors who left Latin America to live in Europe at the end of the 20th century and the beginning of the 21st century. Iwasaki has created an abundant, heterogeneous and erudite work where he explores identity, humor and eroticism, among others. The stories in El cóndor de Père-Lachaise (2019) are examples of originality at the stylistic and formal level. In this article we will analyze three elements of the work related to transculturation, transnationality and intertextuality.